ACARDIUS ACEPHALUS MONSTER IN A GOAT - PATIL, AD; SAHATPURE, SK; BANTE, N; LAKDE, C; GAHLOD, BM (The Indian Journal of Animal Reproduction, 2017)
A goat with dystocia was presented and the fetus was removed after mild traction. The fetus was diagnosed as a monster namely acardius acephalus. The radiographic and postmortem examination of the monster was carried out and the findings were discussed.